Excited state vibrational spectra of all-trans retinal derivatives in solution revealed by pump-dfwm experiments - Kraack, Jan Philip; Motzkus, Marcus; Buckup, Tiago (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2018)
The ultrafast structural changes during the photoinduced isomerization of the retinal-protonated Schiff base (RPSB) is still a poorly understood aspect in the retinal’s photochemistry. In this work, we apply pump-degenerate four-wave mixing (pump-DFWM) to all-trans retinal (ATR) and retinal Schiff bases (RSB) to resolve coherent high- and low-frequency vibrational signatures from excited electronic states. We show that the vibrational spectra of excited singlet states in these samples exhibit pronounced differences compared to the relaxed ground state.